Pendidikan adalah pilar utama da PERAN KEPEMIMPINAN TRANSFORMASIONAL KEPALA SEKOLAH DALAM MENINGKATKAN MUTU PENDIDIKAN - Ridiyawati, Anita Ema; Hansen Lutfiartha; Eko Saparudin; Ngurah Ayu Nyoman M (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the study is to learn how the school principal's leadership in transformational leadership can help to improve the quality of education. Kepemimpinan transformasional is crucial to creating a productive and innovative learning environment. This study highlights some important aspects of educational quality, school leadership, and transformational leadership. The analysis's findings indicate that a school's head who implements transformational leadership practices can improve teacher productivity, which helps to raise educational standards. The head of the school who is able to create a positive and inclusive work environment also consistently creates a positive and inclusive work environment. In addition, this study identifies issues that arise while implementing transformational leadership, such as a lack of understanding of changes and the sumber daya. The results of this study indicate that the transformational leadership of the school has a significant impact on the quality of education. As a result, educators must understand and support the development of transformative leadership in schools. It is hoped that this will serve as a foundation for further research on the best practices in educational research and other research.